Can measurement errors explain variance in the relationship between muscle- and tendon stiffness and range of motion?—a blinded reliability and objectivity study - Warneke, Konstantin; Meder, Julia; Plöschberger, Gerit; Oraže, Manuel; Zechner, Maximilian; Jochum, Daniel; Siegel, Stanislav D.; Konrad, Andreas (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Introduction The relationship between range of motion (ROM) and underlying parameters such as stiffness (ST) remains controversial throughout the literature. Therefore, this study aimed to analyze the potential role of accumulated measurement errors and subjective influences through a comprehensive assessment of both systematic and random errors on the correlation between tissue ST and ROM. Methods A total of 75 subjects participated in this double-blinded reliability evaluation. Besides muscle thickness assessments, lower legs’ ST in the calf muscle and Achilles tendon (shear-wave elastography [SWE] and viscoelastic parameters [MyotonPRO], respectively) were correlated with ankle dorsiflexion ROM (knee-to-wall test [KtW]). Results Ultrasound image acquisition (i.e., muscle thickness and ST) and myotonometry showed intrasession reliability (ICC = 0.93–0.99 and 0.72–0.99, respectively) depending on the device. Only for MyotonPRO, there were meaningful systematic and random errors only for decrement (SEM = 0.002–10.629; MAE = 0.01–24.84). ROM showed ICC > 0.99, while for all parameters interday reliability declined (ICC = 0.395–0.88). Interrater objectivity showed ICC = 0.61–0.91 for ultrasound analysis and 0.66–0.96 for myotonometry. No agreement (ICC = 0–0.09) between different ST measurements was observed, while relationship between ST and ROM depended on the investigator ( r  = 0.21–0.26 versus r  = − 0.02–−0.07). Discussion While aligned with reliability and objectivity metrics from the literature, our results demonstrate that ST determination is device-dependent, and its relationship with ROM varies by measurement day and investigator. This underlines clinically relevant measurement errors in ST evaluation, calling for advance standardization to improve reliability and objectivity, while measurement errors quantified beyond the ICC must not be neglected in future studies.
Keywords: Shear-wave Elastography; Myotonometry; Range Of Motion; Interday Reliability; Bland-Altman Analysis